2005
DOI: 10.1177/107110070502600601
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Tendon Insufficiency: Which Ligaments are Involved?

Abstract: Ligament involvement is extensive in PTTI, and the spring ligament complex is the most frequently affected. Because ligament pathology in PTTI is nearly as common as posterior tibial tendinopathy, treatment should seek to protect or prevent progressive failure of these ligaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
182
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 24 publications
8
182
2
3
Order By: Relevance
“…20 The superomedial and inferomedial calcaneonavicular, talocalcaneal interosseous, plantar naviculocuneiform, plantar first metatarsocuneiform, and anterior superficial deltoid ligaments were attenuated with multiple longitudinal incisions parallel to the fiber orientation. Attenuation was continued by cyclic axial loading using an ElectroForce 3400 axial testing frame (Bose, Minnetonka, MN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The superomedial and inferomedial calcaneonavicular, talocalcaneal interosseous, plantar naviculocuneiform, plantar first metatarsocuneiform, and anterior superficial deltoid ligaments were attenuated with multiple longitudinal incisions parallel to the fiber orientation. Attenuation was continued by cyclic axial loading using an ElectroForce 3400 axial testing frame (Bose, Minnetonka, MN).…”
Section: Methodsmentioning
confidence: 99%
“…6,14,15,[17][18][19] Sectioning simulates complete rupture, which does not typically occur in vivo. 20 Attenuation of ligaments and tendons followed by cyclic axial loading has been used to simulate progressive development of soft tissue laxity. 5,16,21 Deland et al 20 recently reported MRI data showing which ligaments become attenuated in adult acquired flatfoot.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, there is more than 30 % talonavicular uncoverage (Fig. 2), determined by a more substantial failure of the spring ligament and secondary restraints of the arch [2]. This results in greater forefoot abduction.…”
Section: Stagingmentioning
confidence: 99%
“…However, AAFD results from a combination of PTT insufficiency and failure of both capsular and ligamentous structures of the foot. The spring ligament (ie, calcaneonavicular) is the most frequently affected [2], often leading to a combined plantar sag or forefoot abduction through the talonavicular and subtalar joints. Consequently, a combination of plantar and medial migration of the talar head leads to flattening of the arch as the foot displaces from underneath the talus [3].…”
Section: Introductionmentioning
confidence: 99%